2017
DOI: 10.1186/s13287-017-0723-y
|View full text |Cite
|
Sign up to set email alerts
|

Pentosan polysulfate binds to STRO-1+ mesenchymal progenitor cells, is internalized, and modifies gene expression: a novel approach of pre-programing stem cells for therapeutic application requiring their chondrogenesis

Abstract: BackgroundThe pharmaceutical agent pentosan polysulfate (PPS) is known to induce proliferation and chondrogenesis of mesenchymal progenitor cells (MPCs) in vitro and in vivo. However, the mechanism(s) of action of PPS in mediating these effects remains unresolved.In the present report we address this issue by investigating the binding and uptake of PPS by MPCs and monitoring gene expression and proteoglycan biosynthesis before and after the cells had been exposed to limited concentrations of PPS and then re-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In accordance with the literature, our study showed that mice treated with PPS appeared to have better myocyte regeneration and less cartilage damage when compared to CHIKV-infected untreated animals ( S3 Fig ). More recently, the same group demonstrated that PPS enhances chondrogenesis by altering genetic and proteomic signatures leading to increased proliferation of MSCs [ 32 ]. It is possible that similar mechanisms are responsible for the protection against muscle and cartilage damage seen in CHIKV-infected PPS-treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the literature, our study showed that mice treated with PPS appeared to have better myocyte regeneration and less cartilage damage when compared to CHIKV-infected untreated animals ( S3 Fig ). More recently, the same group demonstrated that PPS enhances chondrogenesis by altering genetic and proteomic signatures leading to increased proliferation of MSCs [ 32 ]. It is possible that similar mechanisms are responsible for the protection against muscle and cartilage damage seen in CHIKV-infected PPS-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the growth factor functional group had the greatest number of our top DEGs (13/50) meaning it is the group which saw the most modulated genes from PPS treatment. Moreover, it is known that PPS can stimulate MSCs in vitro [ 31 , 32 ]. Perhaps this mechanism occurs via one of the newly identified growth factors and leads to decreased cartilage damage during CHIKV infection.…”
Section: Discussionmentioning
confidence: 99%
“…PPS is thus chondroprotective and there is a well-documented rationale for its use in the treatment of OA and RA [ 6 ]. Furthermore, PPS promotes proliferation and differentiation of bone marrow stromal mesenchymal stem cells to a chondrogenic phenotype [ 77 , 158 ]. PPS-stimulated chondroprogenitor stem cells have been used to treat OA cartilage [ 159 ].…”
Section: The Chondroprotective Properties Of Ppsmentioning
confidence: 99%
“…PPS localizes in the nucleus of stromal stem cells, promotes development of chondroprogenitor cell lineages, ECM synthesis and discal repair by resident disc cells, offering new opportunities in discal repair biology [ 61 ]. In culture, PPS rapidly binds to MSC surface receptors, and is internalized and localized to the nucleus, inducing cell proliferation and differentiation, and facilitating expansion of chondroprogenitor cell lineages with improved proteoglycan synthesis and ECM synthesizing profiles [ 158 ]. Priming of MSCs with PPS enhances chondrogenesis and MSC proliferation by modifying basal gene and protein expression and offers a means of programming chondroprogenitor MSC lineages of potential application in the repair or regeneration of cartilaginous tissues in OA and degenerative disc disease [ 158 ].…”
Section: Pps and Stem Cells Used In The Repair Of The Degenerate Ivdmentioning
confidence: 99%
“…Aggrecan, hyaluronic acid, and other GAG-based hydrogel systems and their biomimetic equivalents are needed moving forward. There is significant research in this regard applied to cartilage engineering [201][202][203][204][205][206][207][208][209][210], including systems that can be localised within ECM tissue through the incorporation of HA-specific binding peptides [201,205,206] and via steric interactions with collagen type VI and perlecan [211]. Some of these systems have been applied to the IVD [212], most notably in the case of a cytocompatible large aggrecan mimic, which has been chemically, structurally, and mechanically characterised and injected ex vivo into bovine NP tissue [211].…”
Section: Development Of Biomimetic Systems For the Delivery Of Matrix...mentioning
confidence: 99%